Symington for President Biltmore Hotel
The following has been released at Washington, D. C.: Washington, D. C.--George M. Harrison, President of the Brotherhood of Railway Clerks, AFL-CIO, and James B. Carey, President of the International Union of Electrical, Radio and Machine Workers, AFL-CIO, today made the following statement in connection with the candidacy of U. S. Senator Stuart Symington for the President of the United States.